Ferromagnetic quantum criticality in the alloy CePd1-xRhx - Sereni, J.G. (2007)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina